Perceptions And Intentions Of MSME Operators Regarding The Use Of QRIS As A Payment System In Medan - Aulia Safrin, Feby; Harahap, Kartini (Cita konsultindo, 2025)
This study analyzes the perceptions and intentions of Micro, Small, and Medium Enterprise (MSME) operators in Medan regarding the use of QRIS as a digital payment system. Using a qualitative approach, data were collected through in-depth interviews and Focus Group Discussions (FGDs) with MSME operators who had adopted or had yet to adopt QRIS. The findings indicate that perceived Usefulness, ease of use, and risks significantly influence QRIS adoption. MSME operators who recognize transaction efficiency and improved financial record keeping tend to be more receptive to QRIS, while concerns about security and system disruptions remain barriers. Additionally, external factors, such as digital literacy and government support, also contribute to users' intentions to adopt a QRIS. This study emphasizes the need for education and infrastructure improvements to accelerate QRIS adoption among MSMEs.